6x-4=3x+(-4)

Simple and best practice solution for 6x-4=3x+(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-4=3x+(-4) equation:



6x-4=3x+(-4)
We move all terms to the left:
6x-4-(3x+(-4))=0
We calculate terms in parentheses: -(3x+(-4)), so:
3x+(-4)
We add all the numbers together, and all the variables
3x-4
Back to the equation:
-(3x-4)
We get rid of parentheses
6x-3x+4-4=0
We add all the numbers together, and all the variables
3x=0
x=0/3
x=0

You can always share this solution

See similar equations:

| X+3+2x=×+20 | | 9x+x5=6X5 | | 5x-7=3+11 | | 5x2x=28 | | x-14/7=12 | | 7x-6/6x=9 | | A=23+4(x-2) | | 2x+×+4+2x=2x+15 | | 3(x-3)+16=2(x+3) | | 255-m=94 | | 1/5(8t-7)=t+7/10 | | 2x+8+x=2×+15 | | 5=5(v+4) | | (2b-3)/7-b/2=(b+3)/14 | | (2b-3)/7-b/2=b+3/14 | | 4s*4=64s= | | 3n+12+23+4n=210 | | 3n+15+2n+15=180 | | 8n-8+4n=52 | | 5x-(2x-10)=45 | | -68=-4(5n+7) | | 4(m-1)=-(1-4m) | | 20.2+d=23 | | 1x+10=-25+6x | | 5x+9=-7x-111 | | 20*1/5+d=23 | | 7x-7=-1x-47 | | 9(14-t=-117 | | 30m+25=-20+1000 | | 1x+1=-14-4x | | 18=11v-8v | | 9+3x=5x+103/11 | | 4(3y-5)=13 | | 1x+1=37-2x | | 7x+7=-5x+19 | | 7x+5=4x-25 | | 5220=(n-2)180 | | 9x-9=-7(x=1) | | 36.75x+28.50=0.75x | | 4(u+3)-6u=32 | | 3^x-2=43 | | 11-12-29=a | | 6.2÷(2x+1)=21/3÷4 | | 2x-3(2-8x)=2×+22 | | 6.2÷(2x+1)=21 3÷4 | | 6.2/(2x+1)=21/3/4 | | 3(x-5)=4x-2(x+5) | | 10x-4(3-5x)=2(5-x) | | -9(y+9)=-40 | | 3.1x=-5/12 | | 1.6+0.4y+2y-(16)=0 | | 10x+6(6-x)=2x-14 | | 6(5x+4)-8=7+2(3-3x) | | -25=-2(9a+6) | | 82=42/x | | 7n^2+2407n-45594=0 | | -15=9d-5d | | 2?x-5?^2=17 | | 7(7-m)=105 | | 1.6+0.4y+2y=16 | | 5y-7+4y=22 | | 4(3-x)-2(x-5)=4x+7(2x-5) | | x-13.25=24.50 | | 7(3x-2)-2(x-4)+3=0 | | 2y-6.4=y+10 |

Equations solver categories